Acute ST-Elevation Myocardial Infarction in Young in Shahid Gangalal National Heart Centre, Kathmandu, Nepal - Adhikari, Chandra Mani; Manandhar, Reeju; Prajapati, Dipanker; Dhungana, Murari; Hirachan, Anish; Shrestha, Monika; Basnet, Manjila; Tamrakar, Binita; Rajbhandari, Sujeeb (Journal of Advances in Internal Medicine, 2017)
Background and Aims: Acute ST elevation myocardial infarction (STEMI) is often present in old populations. STEMI in young has significantly increased in recent years. We aim to study the conventional risk factors, clinical presentation, management and outcome of Acute STEMI in young patients. Methods: Medical records of all the young patients (aged less than 45 years), who were admitted in our hospital with the diagnosis of Acute STEMI and treated in between 1st July 2015 to 30th June 2016, were retrospectively reviewed. Demographics, conventional risk factors, clinical presentation, management and outcome were recorded. Results: There were total 1211 patients admitted for Acute STEMI, among them, 132(10.9%) were young patients, age ranged from 24 to 45 years with mean age 39.1±4.8 years, with 110 males. Anterior wall MI 50(37.8%) was the most common MI. Symptom onset to arrival to hospital ranged from 1 hour to 144 hours with mean of 19.4±2.4hours. Primary PCI was the mode of reperfusion in 59(44.6%) patients; thrombolysis was done in 19(14.3%) patients. The most common conventional risk factor was tobacco consumption; present in 91(68.9%) patients. Tobacco consumption was the only conventional risk factors in 27(20.4%) patients. There were four (4%) in-hospital mortality. Among the discharged patients all patients received Aspirin, Clopidogrel and Statin. Betablocker and Angiotensin converting enzyme inhibitor/Angiotensin receptor blocker were prescribed in 99(75%) and 96 (72.7%) patients respectively. Mean left ventricular ejection fraction was 45.5±8.6%, with 99(77.3%) having Ejection Fraction ≥40%. Conclusions: Acute STEMI in young was common in male. Tobacco consumption was significant riskfactor. Acute STEMI in young has good prognosis. Journal of Advances in Internal Medicine 2017;06(02):27-31.